Patient Acceptability of the Yorkshire Dialysis Decision AID (YODDA) Booklet: A Prospective Non-Randomized Comparison Study across 6 Predialysis Services. Issue 4 (July 2016) - Winterbottom, Anna E.; Gavaruzzi, Teresa; Mooney, Andrew; Wilkie, Martin; Davies, Simon J.; Crane, Dennis; Tupling, Ken; Baxter, Paul D.; Meads, David M.; Mathers, Nigel; Bekker, Hilary L.
Background: Patients are satisfied with their kidney care but want more support in making dialysis choices. Predialysis leaflets vary across services, with few being sufficient to enable patients' informed decision making. We describe the acceptability of a patient decision aid and feasibility of evaluating its effectiveness within usual predialysis practice. Methods: Prospective non-randomized comparison design, Usual Care or Usual Care Plus Yorkshire Dialysis Decision Aid Booklet (+YoDDA), in 6 referral centers (Yorkshire-Humber, UK) for patients with sustained deterioration of kidney function. Consenting (C) patients completed questionnaires after predialysis consultation (T1), and 6 weeks later (T2). Measures assessed YoDDA's utility to support patients' decisions and integration within usual care. Results: Usual Care ( n = 105) and +YoDDA ( n = 84) participant characteristics were similar: male (62%), white (94%), age (mean = 62.6; standard deviation [SD] 14.4), kidney disease severity (glomerular filtration rate [eGFR] mean = 14.7; SD 3.7); decisional conflict was < 25; choice-preference for home versus hospital dialysis approximately 50:50. Patients valued receiving YoDDA, reading it on their own (96%), and sharing it with family (72%). The +YoDDA participants had higher scores for understanding kidney disease, reasoning about options, feeling in control, sharing their decision with family. Study engagement varied by center (estimated range 14 – 49%; mean 45%); participants varied in completion of decision quality measures. Conclusions: Receiving YoDDA as part of predialysis education was valued and useful to patients with worsening kidney disease. Integrating YoDDA actively within predialysis programs will meet clinical guidelines and patient need to support dialysis decision making in the context of patients' lifestyle.